Race, Vigilant Coping Strategy, and Hypertension in an Integrated Community. (5th September 2017) - Hines, Anika L; Pollack, Craig E; LaVeist, Thomas A; Thorpe, Roland J
Abstract: BACKGROUND: Vigilant coping refers to individuals who, potentially as a result of experiencing discrimination in the past, proactively prepare for the possibility that they will be discriminated against or mistreated because of their race. The extent to which vigilant coping is linked with hypertension, a highly prevalent condition with well-documented racial/ethnic disparities, remains largely unknown. METHODS: We performed a cross-sectional analysis of data from the Exploring Health Disparities in Integrated Communities (EHDIC) study—Southwest Baltimore ( n = 715). We used a series of multivariate logistic regression models to evaluate vigilance as a potential mediator or moderator of the association between race, discrimination, and hypertension within the context of a racially integrated community. RESULTS: There was no difference in prevalence of hypertension between African-Americans and Whites in this sample (66.8 vs. 66.2; P = 0.86). A higher proportion of African-Americans reported discrimination (41.1 vs. 22.9; P < 0.0001) and vigilance (67.3 vs. 46.9; P < 0.0001) compared to Whites; however, neither measure was associated with hypertension. In stratified analyses, bothersome discrimination alongside vigilant coping was associated with higher odds of hypertension among African-Americans and lower odds among Whites. CONCLUSIONS: Overall, prevalence of hypertension was high and there were no racial differences in this racially integrated community. Discrimination, vigilance, and hypertension were differently associated among African-Americans and Whites. Studying lived experiences in integrated communities may illuminate how structural inequalities impact the health of African-Americans more broadly. Further, raising awareness of social factors as they relate to hypertension may help to inform clinical management of low-income patients.